Mencari Pangan “Lokal”: Suara-suara dari Timur - Firdhan Aria Wijaya; Theresia Pratiwi Elingsetyo Sanubari (Society, 2024)
Calls for local food in Eastern Indonesia are often dominated by sago. Still, this attention is overshadowed by continuously glorifying rice as the primary staple, ignoring regional contexts and cultural identities. Through a collaborative forum called the Food Festival Archipelago (FFA), we engaged students in sharing their stories about local food to explore their experiences, imaginations, and cultural ties to Eastern Indonesian cuisine. Using creative methods such as podcasts, short stories, Instagram posts, and videos, we discovered that Java-centric food politics have distanced students from their local food heritage. This disconnection forces many to rely on elders to rediscover traditional food knowledge, highlighting a critical loss of cultural identity. This initiative amplifies marginalized food narratives and serves as an act of resistance against global hegemony, fostering resilience through re-localization efforts. Furthermore, our findings underscore the importance of strengthening food sovereignty and local cultural identity in policy discussions, addressing the challenges posed by modernization while celebrating the rich culinary heritage of Eastern Indonesia.